2014
DOI: 10.1111/cgf.12357
|View full text |Cite
|
Sign up to set email alerts
|

Opacity Optimization for Surfaces

Abstract: In flow visualization, integral surfaces rapidly tend to expand, fold and produce vast amounts of occlusion. While silhouette enhancements and local transparency mappings proved useful for semi‐transparent depictions, they still introduce visual clutter when surfaces grow more complex. An effective visualization of the flow requires a balance between the presentation of interesting surface parts and the avoidance of occlusions that hinder the view. In this paper, we extend the concept of opacity optimization t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…Still, we argue that stream surface selection and rendering are related but different problems: we have shown that for a variety of data sets a single stream surface does not suffice in representing all flow features, and multiple, but potentially occluding, surfaces are required for a complete representation of the characteristic features of the flow domain. Whereas we use the IRIS rendering approach by Hummel et al [HGH*10] to minimize occlusion, the more recent method by Günther et al [GSM*14] is an even more advanced approach for minimization of surface occlusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, we argue that stream surface selection and rendering are related but different problems: we have shown that for a variety of data sets a single stream surface does not suffice in representing all flow features, and multiple, but potentially occluding, surfaces are required for a complete representation of the characteristic features of the flow domain. Whereas we use the IRIS rendering approach by Hummel et al [HGH*10] to minimize occlusion, the more recent method by Günther et al [GSM*14] is an even more advanced approach for minimization of surface occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…Carnecky et al [CFM*13] take into account findings from cognitive research to improve transparency. Günther et al [GSM*14] use optimization to clear view on important regions of surfaces. All these methods aim exclusively at generating and visualizing stream surfaces at interactive rates.…”
Section: Related Workmentioning
confidence: 99%
“…The above methods did not yet consider the potential occlusion that might be introduced by the geometry. Günther et al [22] adjusted the transparency of surfaces to balance occlusion and visibility. Illustrative flow visualization [7] contributed methods to improve the perception of transparent surfaces, including the angle-based and normal variation mapping of Hummel et al [26], the display of surface slabs and contours by Born et al [6] and the diffusion of silhouettes and halos by Carnecky et al [9].…”
Section: Surface Placement and Selectionmentioning
confidence: 99%
“…For line geometry, Günther et al [20] formulated the adjustment of the line opacity as a global optimization problem with bounded variables. Their approach was later extended to animated lines [21], opacity optimization for surfaces [22] and extinction optimization for volumes [1]. Ament et al [1] approximated the energy and reformulated the minimization in ray space, which enabled a significant acceleration for volume data, which was later carried into point, line and surface geometry by Günther et al [23] in their decoupled opacity optimization.…”
Section: Introductionmentioning
confidence: 99%
“…More advanced rendering techniques are possible, which may be optimized towards a simultaneous perception of the shapes of both G and Q . This includes illustrative approaches, opacity optimization for surfaces [GSM∗14] or a piecewise rendering [ZSL∗16].…”
Section: Future Researchmentioning
confidence: 99%